2004
DOI: 10.5694/j.1326-5377.2004.tb06244.x
|View full text |Cite
|
Sign up to set email alerts
|

The other side of the coin: safety of complementary and alternative medicine

Abstract: Most consumers consider complementary and alternative medicine (CAM) products inherently safe. The growing simultaneous use of CAM products and pharmaceutical drugs by Australian consumers increases the risk of CAM–drug interactions. The Therapeutic Goods Administration (TGA) has a two‐tier, risk‐based regulatory system for therapeutic goods — CAM products are regulated as low risk products and are assessed for quality and safety; and sponsors of products must hold the evidence for any claim of efficacy made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Despite the limitations of the Rawlinson and Thompson classification, it remains in use by many authors as a means to simply classify ADRs. 9 It has been suggested that in addition to the Type A and B reactions outlined above, a third group needs to be acknowledged. These are patients who experience an adverse event, such as nausea or vomiting, and wrongly ascribe this as being because of medication, when in fact it may be part of the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations of the Rawlinson and Thompson classification, it remains in use by many authors as a means to simply classify ADRs. 9 It has been suggested that in addition to the Type A and B reactions outlined above, a third group needs to be acknowledged. These are patients who experience an adverse event, such as nausea or vomiting, and wrongly ascribe this as being because of medication, when in fact it may be part of the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…This has created a challenging situation when it comes to detecting, evaluating, and reporting ADRs, because many patients – and, remarkably, even CAM physicians – believe that these kinds of treatments are not associated with risk [ 5 ]. Patient surveys have suggested that this assumption may be traced to the belief that CAM products are 'natural' and therefore harmless [ 14 ]. Assumptions like these have led to a discrepancy between the growing interest in CAM remedies and the limited data on their potential to cause ADRs [ 13 , 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These negative perceptions about safety of self-management strategies of infertility may look contradicting with the wide use, but it can be explained in light of the pressure from husbands, inlaws and society in general to conceive. A study conducted in Jordan revealed similar findings that in spite of the risk encountered when using herbal medicine with conventional medicine, participants still using them [43]. In addition, the unsuccessful previous trials or decreased potential of conventional medical interventions may lead to that some women become 'desperate' to try anything to achieve the desired motherhood.…”
Section: Discussionmentioning
confidence: 94%